Solution of Some Application of System of Ordinary Initial Value Problems Using Osculatory Interpolation Technique - Al-Abrahemee, K. M. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to find a new method for solving a system of linear initial value problems of ordinary differential equation using approximation technique by two-point osculatory  interpolation with the fit equal numbers of derivatives at the end points of an interval [0, 1] and compared the results with conventional methods and is shown to be that seems to converge faster and more accurately than the conventional methods.